2014
DOI: 10.1002/chin.201438021
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: High‐Pressure Synthesis and Structural Characterization of the Type II Clathrate Compound Na30.5Si136 Encapsulating Two Sodium Atoms in the Same Silicon Polyhedral Cages.

Abstract: Single crystals of clathrate compounds Na 8Si 46 (type I) and Na30.5Si136 (type II) are prepared from mixtures of NaSi and Si in a molar ratio of 1:4 under 5 GPa at 1000 and 800 C, respectively. As revealed by single crystal XRD, Na30.5Si136 crystallizes in the space group Fd3m with Z = 4. The large silicon hexakaidecahedral cages are occupied by two sodium atoms (Na 2@Si28) disordered around the center of the Si28 cages. At temperatures < 90 K, the crystal symmetry of the compound changes from a face-centere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Recently, Yamanaka et al have reported a novel Si clathrate compound, Na 30.5 Si 136 , prepared under high-pressure. 28 2 and 3). These U eq values and their ratios are close to those of Na 2+x Ga 2+x Sn 4−x (x = 0.24) (U eq = 0.079(3) Å 2 (Na), 0.01911(18) Å 2 (Ga/Sn), U eq (Na)/U eq (Ga/Sn) = 4.1).…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…Recently, Yamanaka et al have reported a novel Si clathrate compound, Na 30.5 Si 136 , prepared under high-pressure. 28 2 and 3). These U eq values and their ratios are close to those of Na 2+x Ga 2+x Sn 4−x (x = 0.24) (U eq = 0.079(3) Å 2 (Na), 0.01911(18) Å 2 (Ga/Sn), U eq (Na)/U eq (Ga/Sn) = 4.1).…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…27 The above-reported results also shed some light on the mechanism of synthesis of Na−Si clathrates at HPHT conditions, observed in previous in situ and ex situ experiments. 11 In fact, the formation of a high-pressure clathrate compound Na 30.5 Si 136 of structural type II encapsulating two sodium atoms in the same silicon polyhedral cages 52 (as compared to one atom in the case of stoichiometric Na 24 Si 136 compound) has been observed at temperatures ∼300 K below the melting point of Na 4 Si 4 (i.e., at ∼800 K). 11 The experimentally established eutectic melting temperature (equilibrium Na 4 Si 4 + Si ↔ liquid) is just ∼50 K lower than that for pure Na 4 Si 4 , 24 which is indicative of the solid-state 47 and Si.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The small cages of sII clathrate can accommodate one Na atom, and up to two Na atoms may reside within the large cages. 54 Na 24 Si 136 through Na 30.5 Si 136 have been observed, 54 showing that in synthesis Na/Si ratio spans 1:4.46−1:5.67. At x Na = 0.23, it is relatively easy to grow single crystals of sII clathrate by cooling from the melt, e.g., from 1170 K at 9.0 GPa.…”
Section: Crystal Growth and Designmentioning
confidence: 99%
“…24,53 Small changes in composition can shift the phase equilibria, and recent results indicate multiple Na occupancy within the clathrate cages of sII, further complicating the phase behavior. 54 Therefore, the target phase of Na 4 Si 24 exists within a fairly narrow P,T,x region to be optimized experimentally. The results of experiments conducted between 8.0−10.5 GPa and 773−1873 K with With Na/Si ratios greater than 1:6 at pressures between 9.0 and 10.5 GPa, sII clathrate is the dominant phase in recovered multianvil experiments.…”
Section: Crystal Growth and Designmentioning
confidence: 99%
See 1 more Smart Citation